Global and Local Perspectives on the Preservation of Linguistic Diversity: A Nepali Experience - Pun, Min (JODEM: Journal of Language and Literature, 2020)
This paper deals with the past studies about preserving and promoting linguistic diversity with special reference to indigenous languages of the world in general and of Nepal in particular. It is broadly divided into two major categories viz. global perspectives on linguistic diversity issues and local perspectives on linguistic diversity issues. The global perspectives section is related to conceptualizing the global trends of preserving and promoting linguistic diversity in different regions of the globe. For instance, past studies conducted on indigenous languages of Europe, South Asia (including Sri Lanka, Pakistan and India), Latin America, North America, Africa, and Malaysia were reviewed to identify the research gap for this study. The local perspectives section is related to conceptualizing the Nepali trends of preserving and promoting linguistic diversity in Nepal. Similarly, empirical studies were reviewed into four aspects such as a) linguistic diversity and multilingualism, b) endangerment of indigenous languages, c) bilingual and multilingual education, and d) mother tongue literacy. Based on these observations, this paper has been developed to identify the global and local perspectives on the preservation of linguistic diversity, using a Nepali experience.